Phantasmagoria - Villasis, Enrique S. (Likhaan: The Journal of Contemporary Philippine Literature, 2023)
The poems in this collection are products of our weekly online writing prompts. This writer interrogated the tropes and imageries found in popular fantasy and sci-fi series and local legends and framed them as poetic devices for nostalgia, memory, dreams, and grief.